Pengaruh Lingkungan Keluarga Terhadap Perokok Elektrik - Putri, Monifa (Published by Institut Teknologi Pendidikan Indonesia, 2023)
Cigarettes are not something foreign to society, currently many conventional smokers have changed to electric smokers. Not only men, women are also starting to become e-smokers. They have various reasons for choosing electronic cigarettes, including because they look cool, macho, more authoritative/mature, respected by other people, cool and great. Apart from that, smoking behavior can also be influenced by family, peer and social environments. Therefore, it is necessary to know the influence of the family environment on e-smoking among students at the Indragiri Institute of Technology and Business. The research method used is analytical with a cross sectional approach. The results showed that of the 96 students, 9.4% were e-smokers, 72.9% were female. The results of the family environment chi square test obtained a p value of 0.00. The conclusion of this research is that there is an influence between the family environment on e-smoking among students at the Indragiri Institute of Technology and Business.